The relationship between motor skills, perceived self-competence, peer problems and internalizing problems in a community sample of children - Mancini, Vincent; Rigoli, Daniela; Roberts, Lynne; Heritage, B.; Piek, Jan (Wiley InterScience, 2017)
Poor motor skills have been associated with a range of interpersonal and intrapersonal difficulties, including poor self-competence, peer problems, and internalizing problems such as anxiety and depression. The Elaborated Environmental Stress Hypothesis provides a theoretical framework for understating these relationships. Studies have recently begun to evaluate this framework; however, ongoing empirical investigation is required. Currently, the extent to which these relationships may differ across factors such as gender remains unclear. The current study tests an indirect effect of motor skills on internalizing problems via peer problems and perceived self-competence in a community sample of 164 children (81 males; 83 females) aged 7 to 12 years. A combination of clinician-administered, self-report, and parent-rated measures were used. Regression analysis using PROCESS indicated that the relationship between motor skills and internalizing problems was not moderated by gender. Motor skills did have an indirect effect on internalizing problems via perceived scholastic competence and peer problems. Results provide partial support for part of the Elaborated Environmental Stress Hypothesis; perceived scholastic competence and peer problems are mechanisms through which motor skills are related to internalizing problems in school-aged children. This study highlights potentially important targets for psychomotor interventions for this age group. Highlights: The Environmental Stress Hypothesis suggests that motor skills may have an indirect effect on internalizing problems via factors such as peer problems and perceived self-competence. A community sample of 164 children aged 7-12 years provided measures of motor skills and psychosocial functioning. Motor skills had an indirect effect on internalizing problems via perceived scholastic competence and peer problems. This relationship was not moderated by gender.